PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI KECAMATAN SITUBONDO KABUPATEN SITUBONDO - Selfy AN Hardianti; Farida Hanum (ACTON, 2018)
The purpose of this study was to determine the effect of the work environment on employee job satisfaction in Situbondo District, Situbondo Regency. This study uses quantitative design. Saturated samples were 31 respondents. The analytical method used is Validity Test, Reliability Test, Simple Regression Analysis, Partial Test (t-test) and Determination Coefficient Test (R2). The results showed that there was a significant and positive influence between the work environment on employee job satisfaction, with a significant level of 0,000 smaller than the alpha probability level of 0.05, so that partially the work environment variable had a significant effect on employee job satisfaction.